SYSTEMATIC REVIEW OF MPOX SEROPREVALENCE IN NIGERIA: EPIDEMIOLOGY, DEMOGRAPHICS, RISK FACTORS, AND CONTROL - Chinwe Grace Azuka; Kwarbai Aaron Maitala; Adamu Ishaku Akyala; John Etim Edet; Abah Michael Idoko (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
Mpox is a re-emerging zoonotic disease caused by a double-stranded DNA virus of the genus Orthopoxvirus. Since 2017, Nigeria has witnessed a resurgence of Mpox, with outbreaks of increasing magnitude. This study analyzed surveillance data from the Surveillance Outbreak Response and Management System (SORMAS) spanning September 2017 to February 2025, to describe the epidemiology of Mpox and assess implications for surveillance and response. A total of 5,979 suspected cases were reported, of which 1,303 (21.8%) were laboratory-confirmed. Males accounted for 63% of suspected and 65.9% of confirmed cases, while females comprised 37% and 34.1% respectively. The largely affected age group was 20–29 years (47.7% of confirmed cases), reflecting vulnerability among post-smallpox vaccination cohorts. Children under 15 years represented 16% of confirmed cases. Temporal trends revealed outbreak peaks in 2017, 2022, and 2024, suggesting repeated waves and ongoing endemic transmission. Five states (Sokoto, Akwa Ibom, Lagos, Ogun, and Ondo) contributed ~60% of cases, indicating geographic clustering. The overall case fatality rate (CFR) was 7.8%, with slightly higher mortality among females (8.1%) and children (8.2%). Risk factor analysis highlighted both occupational exposure (business/traders, students, farmers) and household clustering (housewives, infants). However, only 9.6% of suspected and 5% of confirmed cases reported contact with an infectious source, underscoring weak case investigation. Surveillance through SORMAS improved data capture and timeliness but was limited by underreporting, incomplete exposure data, and diagnostic bottlenecks. Findings emphasize the need for enhanced One Health surveillance, decentralized diagnostics, community-driven reporting, and targeted risk communication. This study concludes that Mpox in Nigeria has transitioned from sporadic spillover to sustained endemic transmission. Strengthening surveillance and response systems is critical to reducing morbidity, mortality, and the risk of further international spread.